Applying Ibn Khaldun’s Theory Into The Islamic Preaching’s Movement in The Period of Demak Empire: Reflection for the Contemporary Muslim Society - Luhtitianti, UI Ardaninggar; Arifin, Achmad Zainal (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
Ashabiyah and Mulk are positioned as driving forces within the broader framework of Ibn Khaldun’s theory on the rise and fall of dynasties. While many studies have explored Ashabiyah and Mulk, limited efforts have been made to apply these concepts to empirical phenomena in various societies. This paper aims to bridge this gap by applying Ibn Khaldun’s theory to the historical role of saints’ da’wa and their alliances with rulers during the era of the Demak Empire. This research employs a qualitative approach using literature studies, with primary sources including Ibn Khaldun’s Muqaddimah and secondary sources from related scholarly articles. The analysis reveals that Ibn Khaldun’s theory effectively explains the decline of the Demak Empire, attributed to the weakening of Ashabiyah among its ruling elite. Furthermore, this study demonstrates the continued relevance of Ashabiyah and Mulk in analyzing socio-religious phenomena in both historical and contemporary Muslim societies. This research contributes to the academic discourse by offering a practical application of Ibn Khaldun’s theoretical framework to historical and sociological analysis, highlighting its utility in understanding the dynamics of social cohesion and governance. It also underscores the enduring relevance of classical Islamic thought in contemporary contexts.